To derive the explicit formula for the recursive arithmetic sequence defined by \( f(1) = 6 \) and \( f(n + 1) = f(n) + 5 \) for \( n \geq 1 \), we can follow the steps given:
Step 1: Find the Slope
From the terms given in the sequence:
- \( f(1) = 6 \)
- \( f(2) = 11 \)
- \( f(3) = 16 \)
- \( f(4) = 21 \)
The difference between consecutive terms can be calculated as follows:
- \( f(2) - f(1) = 11 - 6 = 5 \)
- \( f(3) - f(2) = 16 - 11 = 5 \)
- \( f(4) - f(3) = 21 - 16 = 5 \)
The common difference (slope) is 5. Thus, the slope \( m \) is: \[ m = 5 \]
Step 2: Find the Y-Intercept
We can use one of the points from the table, for example \( (1, 6) \), to find the y-intercept \( b \). The slope-intercept form of the equation is: \[ y = mx + b \]
Substituting \( y = f(n) \), \( m = 5 \), and the point \( (x, y) = (1, 6) \): \[ 6 = 5(1) + b \] \[ 6 = 5 + b \] To find \( b \): \[ b = 6 - 5 = 1 \]
Step 3: Write the Formula as a Function of n
Now, we can write the equation in slope-intercept form: \[ f(n) = 5n + 1 \]
Conclusion
Thus, the explicit formula that represents the sequence \( f(n) \) is: \[ f(n) = 5n + 1 \quad \text{for } n \in \mathbb{N} \]
This completes our formulation for the recursive arithmetic sequence.